Retrieval under stress decreases the long-term expression of a human declarative memory via reconsolidation - Fernández Larrosa, Pablo Nicolás (2017)
Acute stress impairs memory retrieval of several types of memories. An increase in glucocorticoids, several minutes after stressful events, is described as essential to the impairing retrieval-effects of stressors. Moreover, memory retrieval under stress can have long-term consequences. Through what process does the reactivated memory under stress, despite the disrupting retrieval effects, modify long-term memories? The reconsolidation hypothesis proposes that a previously consolidated memory reactivated by a reminder enters a vulnerability phase (labilization) during which it is transiently sensitive to modulation, followed by a re-stabilization phase. However, previous studies show that the expression of memories during reminder sessions is not a condition to trigger the reconsolidation process since unexpressed memories can be reactivated and labilized. Here we evaluate whether it is possible to reactivate-labilize a memory under the impairing-effects of a mild stressor. We used a paradigm of human declarative memory whose reminder structure allows us to differentiate between a reactivated-labile memory state and a reactivated but non-labile state. Subjects memorized a list of five cue-syllables associated with their respective response-syllables. Seventy-two hours later, results showed that the retrieval of the paired-associate memory was impaired when tested 20 min after a mild stressor (cold pressor stress (CPS)) administration, coincident with cortisol levels increase. Then, we investigated the long-term effects of CPS administration prior to the reminder session. Under conditions where the reminder initiates the reconsolidation process, CPS impaired the long-term memory expression tested 24 h later. In contrast, CPS did not show effects when administered before a reminder session that does not trigger reconsolidation. Results showed that memory reactivation-labilization occurs even when retrieval was impaired. Memory reactivation under stress could hinder -via reconsolidation- the probability of the traces to be expressed in the long term.